Ответы и объяснения

  • Участник Знаний
2013-09-29T11:23:56+04:00
(х-3)/8=4 |•8
х-3=32
х=35

2)(х-3)/8=1/4
4(х-3)=8
4х-12=8
4х=20
х=5

3) (х-3)/8=х
х-3=8х
-7х=3
х=-2,5

4) (3х-2)/5 - х/3=2 |•15
3(3х-2)-5х=30
9х-6-5х=30
4х=36
х=9

5) (х-5)/2=3х
х-5=6х
5х=-5
х=-1

6) (х-1)/8 - (х-5)/3=1/2 |•8•3•2
6(х-1)-16(х-5)=24
6х-6-16х+80=24
-10х=-50
х=5

7) (х-1)/8=(х-5)/3 |•24
3(х-1)=8(х-5)
3х-3=8х-40
-5х=-37
х=7,4

8) (2х-1)/3 -х/2=1|•6
2(2х-1)-3х=6
4х-2-3х=6
х=8

9) (х+4)/2 -1= (х+1)/3 |•6
3(х+4)-6=2(х+1)
3х+12-6=2х+2
х=-4

10) (х-8)=х/2
2(х-8)=х
2х-16=х
х=16